2005
DOI: 10.1183/09031936.05.00096104
|View full text |Cite
|
Sign up to set email alerts
|

Early gastrostomy reduces the rate of ventilator-associated pneumonia in stroke or head injury patients

Abstract: Presence of a nasogastric tube is a risk factor for the development of ventilatorassociated pneumonia (VAP). Alternatively, gastrostomy can be used for administration of enteral feedings.To determine whether early performance of gastrostomy affects frequency of VAP, a randomised, controlled study was carried out in patients mechanically ventilated for stroke or head injury. In the gastrostomy group, patients underwent the procedure within 24 h of intubation. A nasogastric tube was inserted in controls. Individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
11

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 33 publications
0
37
0
11
Order By: Relevance
“…Overall, cultures often remain negative without bacterial growth [15,48]. Staphylococcus aureus which resides in the nasal cavity, and aerobic Gram-negative bacilli including Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter baumannii were the most frequently isolated pathogens in the studies identified by our search [11,14,15,23,48,49,50,51]. These findings are consistent with the results of a recent meta-analysis of stroke-associated infections which often showed negative cultures or the same above-isolated pathogens in addition to Escherichia coli and Enterococcus species, while Streptococcus species were occasionally isolated [52].…”
Section: Microbiologic Datamentioning
confidence: 99%
“…Overall, cultures often remain negative without bacterial growth [15,48]. Staphylococcus aureus which resides in the nasal cavity, and aerobic Gram-negative bacilli including Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter baumannii were the most frequently isolated pathogens in the studies identified by our search [11,14,15,23,48,49,50,51]. These findings are consistent with the results of a recent meta-analysis of stroke-associated infections which often showed negative cultures or the same above-isolated pathogens in addition to Escherichia coli and Enterococcus species, while Streptococcus species were occasionally isolated [52].…”
Section: Microbiologic Datamentioning
confidence: 99%
“…First, oropharyngeal cultures (we assume that these are meant by ''respiratory secretions'', at least when referring to younger children) might not be as representative for defining bacterial colonisation of a CF lung as bronchoalveolar lavage fluid cultures [4]. Secondly, as actually shown by one of the authors of this paper, the time for immune responses after the onset of chronic PA lung infection differs from patient to patient and from antigen to antigen with reported mean times of 6-15 months [5]. Consequently, it might be misleading to rely on serum anti-PA antibodies for exclusion of PA infection in the short term.…”
Section: Eradication Of Pseudomonas Aeruginosa In Cystic Fibrosismentioning
confidence: 84%
“…We speculate that the advantage of performing an early gastrostomy is the possibility of avoiding dysfunction of lower oesophageal sphincter due to the presence of a nasogastric tube [5]. JOHNSON et al [6] have demonstrated an increase in lower oesophageal sphincter pressure following performance of percutaneous endoscopic gastrostomy and a decrease in gastro-oesophageal reflux score.…”
Section: From the Authorsmentioning
confidence: 99%
“…Brain injury, severe stroke and unconsciousness, due to sedatives and hypnotics, disturb the swallowing reflex. This results in the development of aspiration pneumonia in humans and animals [5]. However, nosocomial pneumonia and aspiration pneumonia are prevented by the improvement of the swallowing reflex after administration of angiotensin-converting enzyme (ACE) inhibitors [6].…”
Section: To the Editorsmentioning
confidence: 99%